ANALISIS AKSESIBILITAS RAMAH LANSIA PADA DESTINASI WISATA RELIGI MAKAM AIR MATA IBU DI KABUPATEN BANGKALAN DALAM PERSPEKTIF MAQASHID SYARIAH - Besri; Ali Hisyam, Mohamad (Journal of Islamic Economic and Law (JIEL), 2024)
Maqashid sharia are the main goals that Islamic sharia wants to achieve. Maqashid sharia aims to ensure the welfare of the people by protecting five elements: religion, soul, reason, lineage and property. This is an important basis in ensuring the facilities and infrastructure provided for the elderly in that location. From a maqashid sharia perspective, fulfilling this accessibility not only supports the physical well-being of the elderly, but also supports their rights to carry out their worship comfortably and safely. The research method used is qualitative with a descriptive approach, where data is collected through direct observation, in-depth interviews with tourism managers, and documents. The aim is to gain an in-depth understanding of the phenomenon being studied, and describe the situation or behavior in detail, as well as explore the views and experiences of the research subject thoroughly and in context. This research aims to analyze accessibility Makam Air Mata Ibu in Bangkalan Regency from a maqashid sharia perspective. To ensure that the facilities provided not only meet physical standards but are also in line with sharia principles which emphasize the protection and welfare of all individuals.